Vitamin D Postpartum Concentrations: Relationship with Nutritional Condition and Morbidities during Pregnancy - Maria Eliana Pierre Martins; Carmem Ulisses Peixoto Esmeraldo; João Paulo Duarte Sabiá; João Hallisson Lemos Carvalho; Fabíola Isabel Suano-Souza; Roseli Oselka Saccardo Sarni (Hindawi Limited, 2018)
Objective. To evaluate postpartum vitamin D deficiency/insufficiency and to relate it to pregestational BMI, gestational weight gain, and sociodemographic variables. Methods. This is a cross-sectional study with 225 full-term pregnant women. Data collected are as follows: maternal health, socioeconomic status, pregestational body mass index (BMI), and gestational weight gain. Laboratory evaluation included vitamin D [25(OH)D], calcium, phosphorus, magnesium, and alkaline phosphatase. Results. The mean age of women was 25.6±6.6 years. Dark skin color, low education, and work in the urban region were predominant. Regular sun exposure, photoprotection, and vitamin D supplementation were reported by 144 (64.0%), 44 (19.6%), and 5 (2.2%) women, respectively. The mean plasma concentrations of 25(OH)D were 26.0±6.8 ng/mL. Levels compatible with deficiency (<20 ng/mL) and insufficiency (20-30 ng/mL) were observed in 43 (19.1%) and 124 (55.1%) women, respectively. The increase of 1 ng/mL in 25(OH)D concentrations was associated with an increase of 0.16 mg/dL (95%CI 0.19 to 2.02; p=0.018) for calcium. There were no associations with 25(OH)D concentrations with pregestational BMI and with gestational weight gain. Conclusions. The high frequency of postpartum vitamin D deficiency/insufficiency in women with a full-term pregnancy in a region with a large and permanent sun exposure reminds us of the need for intervention policies aimed at preventing vitamin D deficiency during pregnancy.